Practicing English through Lesser Strategy by Teaching Reducing Apprehension - Abda, Apraza Pino; Asty, Hervina (TELL - US JOURNAL, 2016)
Lesser strategy is a strategy that helps students manage their thinking or ideas when they want to write some paragraphs in writing process. Not only manage students’ ideas but also explore students’ ideas in making longer writing based on their thinking. Thus, this strategy also guides students how to make list based on students’ thinking before they start writing. It is hoped that after the readers read this paper, the readers are able to use this strategy in the classroom, especially in writing class. Lesser strategy gives concrete procedures of constructing an essay. That is why the writer would like to give some suggestions for English teacher, and also candidates of teacher. For English teacher, it is very useful to introduce and to apply lesser strategy in teaching writing at Senior High School because this strategy can help English teacher and also the students to understand the main point of an essay in order to help the students are able to write by using the lesser strategy’s steps, because it has simple steps that is easy to be implicated for all the students in writing class.